Learning of bimanual motor sequences in normal aging - Bhakuni, Rashmi; Mutha, Pratik K. (Frontiers in Aging Neuroscience, 2015)
While it is well accepted that motor performance declines with age, the ability to learn simple procedural motor tasks appears to remain intact to some extent in normal aging. Here we examined the impact of aging on the acquisition of a simple sequence of bimanual actions. We further asked whether such learning results from an overall decrease in response time or is also associated with improved coordination between the hands. Healthy young and old individuals performed a bimanual version of the classic serial reaction time task. We found no learning deficit in older adults and noted that older subjects were able to learn as much as young participants. We also observed that learning in both groups was associated with an overall decrease in response time, but switch cost, the increase in response time when a switch in hands was required during sequence execution, did not decrease with learning. Surprisingly however, overall switch cost was lower in the older group compared to the younger subjects. These findings are discussed in the context of interactions between procedural and declarative memory, reduced interhemispheric inhibition and more symmetric cortical activation during motor performance in normal aging.